First multiply together and list the factors of independent terms.
Now find a pair that adds to x coefficient. If you cannot find such a pair then the trinomial does not factor.
Rewrite the middle term as a sum of terms whose coefficients are the chosen pair and factor by grouping.
Factor: x2+ -4x + -12.
Here the given expression x2 -4x -12 can be rewritten as x2 -6x + 2x -12.
Now group x2 with -6x and 2x with -12.
So it will be =(x2 + -6x) + (2x + -12).
= x ×(x − 6) + 2 × (x − 6).
= (x − 6)×(x + 2).
So x = 6 and x = -2.
x = 6 and x = -2.
Factors are: (x - 6) (x + 2) .